The Effect Of Halal Label, Islamic Branding And Product Quality On The Decision To Purchase Pepsodent Siwak By Students Of State Islamic University Of Sultan Aji Muhammad Idris Samarinda - Al Hasrajun; Moh Mahrus; Nur Rahmatullah (Borneo Islamic Finance and Economics Journal, 2025)
The increasing awareness of halal lifestyle among Indonesian consumers has led to a growing demand for halal-certified personal care products. This phenomenon sparked the researcher’s interest in examining the factors that influence consumer behavior in this segment. This study analyzes the influence of Halal Labels, Islamic Branding, and Product Quality on the Purchase Decision of Pepsodent Siwak among students of UIN Sultan Aji Muhammad Idris Samarinda. Using a quantitative approach with multiple linear regression, the research involved 100 respondents from the 2020–2023 cohorts selected through simple random sampling. Data were collected via questionnaires and supporting literature, and analyzed using SPSS 26 through instrument testing, classical assumption testing, and hypothesis testing. The results indicate that the Halal Label does not have a significant effect on purchase decisions (sig. 0.334 > 0.10), while Islamic Branding (sig. 0.04 < 0.10) and Product Quality (sig. 0.00 < 0.10) have a significant partial effect. Simultaneously, the three variables have a significant effect (F-value 78.546, sig. 0.00 < 0.10) with an RÂ² value of 0.697, meaning that 69.7% of the variation in purchase decisions is explained by the model.